First-line platinum-based chemotherapy and survival outcomes in locally advanced or metastatic pulmonary lymphoepithelioma-like carcinoma. (November 2019) - Lin, Zuan; Fu, Sha; Zhou, Yixin; Zhang, Xuanye; Chen, Chen; He, Li-na; Li, Haifeng; Wang, Yuhong; Chen, Tao; Zhang, Li; Hong, Shaodong
Highlights: We report data from the largest cohort of advanced pulmonary LELC patients. Palliative thoracic radiotherapy extends the survival of advanced pulmonary LELC. Gemcitabine-based chemotherapy is active in pulmonary LELC. We revealed key prognostic factors, including EBV DNA and cyles of chemotherapy. Abstract: Objectives: Pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare subtype of primary lung cancer. Due to the lack of prospective studies, the optimal first-line chemotherapy regimens and survival outcomes remain unclear. Materials and methods: This real-world, retrospective study enrolled consecutive patients with unresectable pulmonary LELC. The survival outcomes, prognosis, and comparative efficacy of different chemotherapy regimens were investigated. Results: In total, 127 patients were included in the analyses. The first-line chemotherapy regimens included gemcitabine plus platinum (GP, n = 19 [15.0%]), taxanes plus platinum (TP, n = 70 [55.1%]) and pemetrexed plus platinum (AP, n = 38 [30.0%]). 25 (19.7%) patients underwent palliative thoracic radiotherapy. 60 (47.2%) patients had detectable baseline Epstein-Barr virus (EBV) DNA. For the entire cohort, objective response was obtained in 41 patients (32.3%). Median progression-free survival (PFS) and overall survival (OS) were 7.7 months (95% CI, 6.6–8.8) and 36.7 months (95% CI, 30.9–42.5), respectively. Among the three chemotherapy regimens, GP achieved the highest response rate (GP, 63.2% vs. TP, 30.0% vs. AP, 21.1%; p = 0.005). Median PFS in the GP group (8.8 months) was also significantly longer than that in the TP group (7.9 months) and AP group (6.4 months) ( p = 0.031). In the multivariate model, cycles of first-line chemotherapy (p < 0.001), palliative thoracic radiotherapy ( p < 0.001), and chemotherapy regimens ( p = 0.031) remained independent prognostic factors for PFS; while cycles of first-line chemotherapy ( p = 0.002), baseline EBV DNA ( p = 0.033) and palliative thoracic radiotherapy ( p = 0.041) were significantly associated with OS. Conclusion: Gemcitabine-based chemotherapy and palliative thoracic radiotherapy are active in pulmonary LELC. These data provide added evidence for the similarity between pulmonary LELC and nasopharyngeal carcinoma in endemic area. Randomized controlled studies are needed to further define the standard-of-care for patients with advanced pulmonary LELC.